Real-World Evidence for Long-Term Safety and Effectiveness of Ipragliflozin in Japanese Patients with Type 2 Diabetes Mellitus: final Results of a 3-Year Post-Marketing Surveillance Study (STELLA-LONG TERM). (11th February 2021) - Nakamura, Ichiro; Maegawa, Hiroshi; Tobe, Kazuyuki; Uno, Satoshi
ABSTRACT: Objective: To evaluate the long-term safety and effectiveness of ipragliflozin in real-world clinical practice in Japanese patients with type 2 diabetes mellitus (T2DM). Research design and methods: This post-marketing surveillance study (STELLA-LONG TERM) included Japanese patients newly initiated on ipragliflozin between 17 July 2014 and 16 October 2015 (data lock: 30 September 2019). Survey items included demographics, treatments, adverse drug reactions (ADRs), vital signs, and laboratory variables. Results: Of 11, 424 registered patients, safety and efficacy analysis sets comprised of 11, 051 and 8, 763 patients, respectively. ADRs occurred in 2, 129 patients (19.27%) and serious ADRs occurred in 210 patients (1.90%). Renal and urinary disorders (n = 739, 6.69%), particularly polyuria/pollakiuria (n = 612, 5.54%) and volume depletion-events, including dehydration (n = 243, 2.20%), comprised the most common ADRs. Mean (SD) change in hemoglobin A1c (─0.66 [1.25] %), fasting plasma glucose (─28.8 [50.1] mg/dL) and body weight (─3.33 [4.32] kg) from baseline to 36 months were statistically significant ( P < 0.001). Conclusions: The safety profile of long-term ipragliflozin treatment in routine clinical practice is consistent with previously reported interim data at 12 or 24 months and pre-approval clinical trials. Ipragliflozin treatment was also associated with sustained improvements in efficacy parameters for over 3 years.